The impact of MICB mismatches in unrelated haematopoietic stem cell transplantation - Amann, Elisa Maria; Gowdavally, Sowmya; Tsamadou, Chrysanthi; Platzbecker, Uwe; Sala, Elisa; Wagner-Drouet, Eva; Valerius, Thomas; Kröger, Nicolaus; Wulf, Gerald; Einsele, Hermann; Thurner, Lorenz; Schaefer-Eckart, Kerstin; et al. (HLA, 2024)
MICA polymorphisms have been associated with increased incidence of acute GvHD and adverse outcome in allogeneic haematopoietic stem cell transplantation (HSCT). MICB is another expressed member of MHC class I-related chain genes and its impact on HSCT outcome is yet to be fully defined. We typed a large cohort of patients and donors for MICB polymorphisms and investigated the impact of MICB matching on outcome after unrelated HSCT. 69.2% of the patients were 10/10 human leukocyte antigen (HLA) matched and 30.8% were 9/10 HLA matched. MICB typing was performed using a short amplicon-based NGS typing assay on the Illumina MiSeq platform. Differences in proteins were considered as mismatches. MICA polymorphisms were identified as possible confounder and were therefore included as parameter in the multivariate analyses. Due to the strong linkage disequilibrium with the classical HLA-genes, sub-stratification for HLA matching status was necessary, and no effect of MICB mismatches was seen in the 10/10 HLA matched group when compared to the MICB matched cases. However, in the 9/10 HLA matched group, MICB mismatched cases showed significantly worse disease free survival (DFS), GvHD and relapse free survival (GRFS) compared to the MICB matched cases (DFS: HR 1.24, p = 0.011; GRFS: HR 1.26, p = 0.002). MICA mismatches had no impact on any outcome parameter. According to our findings, effects previously attributed to MICA differences may have been confounded by MICB polymorphisms. We show that MICB differences contribute a small but relevant effect in 9/10 HLA-matched transplantations, which in turn highlights the possible usefulness of MICB typing in donor selection among similarly suitable 9/10 matched donors, especially when HLA-B mismatches have to be accepted.
Online veröffentlicht: 27. Juni 2024
Gesehen am 30.01.2025